The dangers of unsecured voice. Issue 5 (May 2015) - German, Paul
Abstract : The UK's SMEs are increasingly using Voice over Internet Protocol (VoIP) in order to cut call costs. Alongside cloud computing, VoIP is a key component in today's flexible, low-cost infrastructure that is supporting business agility and growth. Yet while businesses are increasingly confident to deploy these technologies, far too many are failing to understand the associated risks.